PENGEMBANGAN DAN PENGUJIAN SISTEM INFORMASI AKADEMIK BERBASIS WEB UNTUK MENINGKATKAN PELAYANAN PADA SEKOLAH SMK - Suhartono Suhartono (semanTIK, 2018)
This study aims to make web-based academic information software and find out the quality of devices according to ISO 9126 includes Functionality Reliability, Portability, and Usability. This research is a type of Research and Development Research (R&D). The object of this research is a Web-based Vocational Academic Information System. This study uses the Waterfall development model with 5 stages of Analysis, Design, Implementation, Testing, and Maintenance. The method used in the data is through Interviews and Questionnaires. Data analysis techniques that are Descriptive Analysis, while for software quality testing according to ISO 9126 standard uses 4 characteristics, namely Functionality, Reliability, Portability, and Usability. Instruments for testing functionality using the Black Box Testing method, reliability using Webserver Stress Tool Software, portability using Browserstack Software, while for use using a complete questionnaire. The results of the functionality for sub-physical Accuracy and Conformity indicate a 100% feasibility level, for different system Security from Malware, Blacklisted Websites, Injected SPAM, Defacement, and SQL Injection, for the results of system reliability testing because the system can run well. both with 5 simultaneous users with an average time of 20 seconds with a success rate of 99.78%. At the beginning of portability, the feasibility rate is 100%, and in usability testing shows a feasibility rate of 84%.Keywords— Academic Information System, Functionality, Usability, Web, ISO 9126.DOI : 10.5281/zenodo.2009427